Snail Shell Waste Threat to Sustainability and Circular Economy: Novel Application in Food Industries - Potortì, Angela Giorgia; Messina, Laura; Licata, Patrizia; Gugliandolo, Enrico; Santini, Antonello; Di Bella, Giuseppa (Sustainability, 2024)
Effective waste management has become an urgent societal challenge. Food waste is made up of items meant for human consumption that are lost, polluted, disposed of, or deteriorated; the reutilization of shells from mollusk waste is a severe problem in terms of environmental protection and the development of the circular economy. The properties of waste shells are presented and discussed, including their biological–natural origin and high calcium carbonate content. This could add social and innovation focus on shell waste management, getting a non-toxic, eco-sustainable, low-cost, biodegradable supplement to invest in. Furthermore, it has the potential to support the circular economy approach by creating a closed system that minimizes the use of natural resources and environmental contamination. This review explores edible mollusk shell waste sources and functional properties of inorganic components of snail shell waste like minerals and active substances like chitin, chitosan, and calcium carbonate and attempts to carry out a comprehensive analysis of the scientific literature published over the last 20 years, elucidating prominent patterns in the utilization of shell waste in food application industry, as additives and supplements development to promote both human and animal health.